CAR RENTAL WEBSITE DESIGN IN MANDIRI LANCAR SOUTH KOREAN USING MACROMEDIA DREAMWEAVER 8 PHP & MYSQL - Paryanto Paryanto; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2002)
It contains a glimpse of the writing about the profile of the car rental. There was also a consumer of data inputting making use of software (software) PHP and MySQL.  Under such circumstances, the writer make an application in accordance with current procedure, this application is expected can assist in overcoming any problems that exist, to provide or obtain necessary information, as well as expected can promote rental cars via the Internet.